Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10517-012-1672-1
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Inflammatory Process in Different Types of Unstable Atherosclerotic Plaques

Abstract: Inflammatory biomarkers and chemoattractants characteristic and important for different types (lipid; inflammatory erosive; degenerative necrotic) of unstable plaques in coronary arteries were identified and studied in male patients with coronary atherosclerosis without acute coronary syndrome we studied. Among the three types of unstable plaques, elevated concentrations of IL-1β, IL-6, IL-8, IL-18 and monocyte chemotactic protein-1 were characteristic of not only inflammatory erosive type, but also lipid type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…20 The CRP is an acute-phase reactant that plays a direct role in the inflammatory process by stimulating monocyte release of inflammatory cytokines such interleukin 1 (IL-1), IL-6, and tumor necrosis factor α. 21 The present study revealed that the value of the myocardial biomarkers CK-MB, cTnI, and hsCRP were all significantly increased after PCI, which is in accordance with the other studies, 16,17 indicating that inflammation plays an important role in PCI-related myocardial injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20 The CRP is an acute-phase reactant that plays a direct role in the inflammatory process by stimulating monocyte release of inflammatory cytokines such interleukin 1 (IL-1), IL-6, and tumor necrosis factor α. 21 The present study revealed that the value of the myocardial biomarkers CK-MB, cTnI, and hsCRP were all significantly increased after PCI, which is in accordance with the other studies, 16,17 indicating that inflammation plays an important role in PCI-related myocardial injury.…”
Section: Discussionsupporting
confidence: 92%
“…Several cytokines take part in inflammatory reactions in the ACS pathophysiology. 16,17 Myocardial damage during PCI is associated with inflammatory response that significantly correlates with cardiovascular risk. Elderly patients with ACS have a greater incidence of multivessel disease and more diseased vessels; also, they have more comorbidities such as diabetes, hypercholesterolemia, hypertension, and renal disease resulting in higher risk of adverse vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of hyperlipidemia may be an important component for the management of atherogenesis in its early stages (2, 3). Several lines of evidence support the notion that atherosclerosis is a chronic inflammatory disease in nature (4–6). The chemokine interleukin‐1β (IL‐1β)/chemokine (C‐X‐C motif) ligand 8 (CXCL8/IL‐8) has been known to play an important role in monocyte migration into the subendothelial space in the early phase of atherosclerosis (7, 8).…”
Section: Introductionmentioning
confidence: 87%
“…CD34 was previously used to identify neovessels and was characterized as a marker of atherosclerosis [ 24 ]. In the present study, we observed that atherosclerotic plaques are rich with microvessels.…”
Section: Discussionmentioning
confidence: 99%